Response of Nezara viridula (Hemiptera: Pentatomidae) terhadap Beberapa Ekstrak Kasar Tanaman - Asmanizar Asmanizar; Aldywaridha Aldywaridha; Edy Sumantri; Ratna Mauli Lubis (Vegetalika, 2020)
Nezara viridula (Hemiptera: Pentatomidae) is an important pest of soybean crop in Indonesia mainly soy bean. The insect cause seed damaged and decreasing of seed quality and quantity. The research was conducted to evaluate the insecticidal potential plant crude extract on the mortality of Green Stink Bug, N. viridula. Plant crude extracts were used in this study extracted by Soxhlet extractor. The experiment was done as oral toxicity (stomach poison) by dipping the bean pod in the crude extract solution and fed to N. viridula adult. The concentrations were 0.5 and 0.25% (volume of extract/volume of solution, v/v). The crude extracts which caused mortality effect up to 90-100% were continued to find the LC50 value.  The results revealed that N. viridula mortality was affected by crude extracts. Crude extract of Annona muricata seed, Alpinia galanga rhizome and Jatropha curcas seed, at 0.5  and 0.25% concentration showed insects mortality up to  97.5-100%. Whilst, crude extracts of Lamtana camara,  Cymbopogon nardus leaf and clumb, and P. betle leaf caused insect mortality 47.50 to 55%. Probit analysis showed that J. curcas seed crude extract was highly toxic (LC50=0.005%) to N. viridula adult followed by A. galanga rhizome crude extract (LC50=0.022%) and A. muricata seed crude extract (LC50=0.031%). These crude extracts proved to be highly potent to control N. viridula. More studies are essential to test these crude extracts and it is potential application as botanical insecticides at screen house and field.